2013
DOI: 10.1148/radiol.13121454
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Multiparametric Prostate MR Images: Differentiation between Prostate Cancer and Normal Tissue and Correlation with Gleason Score—A Computer-aided Diagnosis Development Study

Abstract: The combination of 10th percentile ADC, average ADC, and T2-weighted skewness with CAD is promising in the differentiation of prostate cancer from normal tissue. ADC image features and K(trans) moderately correlate with GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
217
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(237 citation statements)
references
References 52 publications
16
217
2
2
Order By: Relevance
“…AUC values for ADC parameters in discriminating low-from intermediateand high-risk lesions (AUC = 0.821-0.854) also lie within the range of previously reported values for peripheral prostate lesions (Donati et al 2014, Kobus et al 2012, Vargas et al 2011, Turkbey et al 2011, Oto et al 2011, Hambrock et al 2011, Peng et al 2013. One recent study reported a higher value of AUC (0.90) for the median ADC in peripheral zone PCas (Hambrock et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…AUC values for ADC parameters in discriminating low-from intermediateand high-risk lesions (AUC = 0.821-0.854) also lie within the range of previously reported values for peripheral prostate lesions (Donati et al 2014, Kobus et al 2012, Vargas et al 2011, Turkbey et al 2011, Oto et al 2011, Hambrock et al 2011, Peng et al 2013. One recent study reported a higher value of AUC (0.90) for the median ADC in peripheral zone PCas (Hambrock et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…However, studies differ in the specific ADC value used to distinguish between the cancers. The features used have included ADC mean computed from a single slice region of interest (ROI) (15,16,18), ADC mean computed from the entire volume using different sets of diffusion b-values (all vs. fast vs. slow) (19), 10th percentile of the ADC computed from the entire lesion (20), 10th percentile and ADC mean (21), and ADC mean computed over the entire lesion (22). Furthermore, none of the aforementioned studies used more than five imaging features for the analysis.…”
mentioning
confidence: 99%
“…The final approach to analyzing DCE images aims to estimate physiologically interpretable, kinetic parameters by fitting pharmacokinetic models to the enhancement curves [88,113,114]. The most common is the two-compartment model.…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%